O arquiteto e as máquinas: do registro à experimentação - Lauwers, Sara Rodrigues (2023)
The dissertation concerns the transformations in architectural representation through technological advances over time, showing how much representation moves away from being just a record to approach experimentation. First, a contextualization is carried out through a historical bibliographical research about the emergence of architectural representation throughout antiquity until the beginning of the use of technology to represent architecture. Then, it deals with the technological context of the present, starting with the use of digital modeling programs, 3D printers, virtual reality and simulation technologies in architecture. And finally, innovative representation methods and technologies from other areas, still in the study and experimentation stage, with potential for application in architectural representation, which could expand the modus operandi of thinking and representing architecture.